Modulation of Apolipoprotein D levels in human pregnancy and association with gestational weight gain - Lafond Julie; Masse André; Giguère Yves; Forest Jean-Claude; Do Carmo Sonia; Rassart Eric (BMC, 2009)
Abstract Background Apolipoprotein D (ApoD) is a lipocalin involved in several processes including lipid transport, but its modulation during human pregnancy was never examined. Methods We investigated the changes in the levels of ApoD in the plasma of pregnant women at the two first trimesters of gestation and at delivery as well as in the placenta and in venous cord blood. These changes were studied in 151 women classified into 9 groups in relation to their prepregnancy body mass index (BMI) and gestational weight gain (GWG). Results Plasma ApoD levels decrease significantly during normal uncomplicated pregnancy. ApoD is further decreased in women with excessive GWG and their newborns. In these women, the ApoD concentration was tightly associated with the lipid parameters. However, the similar ApoD levels in low cholesterol (LC) and high cholesterol (HC) women suggest that the plasma ApoD variation is not cholesterol dependant. A tight regulation of both placental ApoD transcription and protein content is most probably at the basis of the low circulating ApoD concentrations in women with excessive GWG. After delivery, the plasma ApoD concentrations depended on whether the mother was breast-feeding or not, lactation favoring a faster return to baseline values. Conclusion It is speculated that the decrease in plasma ApoD concentration during pregnancy is an adaptive response aimed at maintaining fetal lipid homeostasis. The exact mechanism of this adaptation is not known.